Análise do Programa de Atenção à Pessoa na Terceira Idade da Universidade Federal de Ouro Preto de 1994 a 1997 - Nuncio Antonio Araujo Sol (1999)
This survey aims at evaluating the program of attention to elderly people developed by the Federal University of Ouro Preto UFOP, through the Physical Education, Clinical Analysis, Clinical and Social Nutrition Departments and Health Center. The survey evaluated doctors handbook of ninety-two members of the Project "Activities in the Third Age, developed by the Physical Education Department, as regards clinic parameters such as systolic and diastolic blood pressure, glicemy fast, total serum cholesterol, HDL cholesterol, LDL cholesterol, uiglycerids, rates of coronary heart disease risks (Castelli I and Castelli II) and rate of Corporal Mass. These parameters were evaluated from January, l994 to June, l997. During the survey the author accompanied the members of the Project in travels taking about two days, the objectives were in increasing the integration with the group and also in increasing knowledge about the group behavior, especially concerning activities related to morbidity risk factors in this age group. Although the high rates of the sub-registers of data checked in the handbooks (mean of 23%), the results showed a relevant statistic reduction of Castelli II in the elderly women. It was not found other alteration statistically significant. The results also showed that there was reduction in the mean rates of the systolic and diastolic blood pressure (in the women), glucose, total serum cholesterol, LDL cholesterol, triglycerids, rates of Castelli I and Castelli II and a increase of mean rates of HDL cholesterol, also there was reduction of obesity and high blood pressure in elderly women and men. Summing up, the results obtained show the necessity of implanting, and carrying out programs like this that takes into consideration the importance of this age group. This sort of program is a good way of influencing in the control and prevention of risk factors. However, the parameters used in the evaluation were not appropriated to the personal perception of the author, because, of the necessity of inclusion of other parameters of evaluation (anthropologic, sociologic, psychological, and so on), that make possible a better approximation of the real correlation between the variety of factors that influence in the quality of living of this people.